Sarsasapogenin alleviates diabetic nephropathy through suppression of chronic inflammation by down-regulating PAR-1: In vivo and in vitro study - Tang, Zhuang-Zhuang; Zhang, Yu-Meng; Zheng, Ting; Huang, Ting-Ting; Ma, Teng-Fei; Liu, Yao-Wu (Phytomedicine (Stuttgart), 2020)
Sarsasapogenin (Sar) shows good effects on diabetic nephropathy (DN) through inhibition of the NLRP3 inflammasome, yet the potential mechanism is not well known. This study was designed to explore the regulation of thrombin and/or its receptor protease-activated receptor 1 (PAR-1) on the NLRP3 inflammasome and NF-κB signaling in DN condition, and further expounded the molecular mechanism of Sar on DN. Streptozotocin-induced diabetic rats were treated by gavage with Sar (0, 20 and 60 mg/kg) for consecutive 10 weeks. Then urine and serum were collected for protein excretion, creatinine, urea nitrogen, and uric acid assay reflecting renal functions, renal tissue sections for periodic acid-Schiff staining and ki67 expression reflecting cell proliferation, and renal cortex for the NLRP3 inflammasome and NF-κB signaling as well as thrombin/PAR-1 signaling. High glucose-cultured human mesangial cells (HMCs) were used to further investigate the effects and mechanisms of Sar. Sar markedly ameliorated the renal functions and mesangial cell proliferation in diabetic rats, and suppressed activation of the NLRP3 inflammasome and NF-κB in renal cortex. Moreover, Sar remarkably down-regulated PAR-1 in protein and mRNA levels but didn't affect thrombin activity in kidney, although thrombin activity was significantly decreased in the renal cortex of diabetic rats. Meanwhile, high glucose induced activation of the NLRP3 inflammasome and NF-κB, and increased PAR-1 expression while didn't change thrombin activity in HMCs; however, Sar co-treatment ameliorated all the above indices. Further studies demonstrated that PAR-1 knockdown attenuated activation of the NLRP3 inflammasome and NF-κB, and Sar addition strengthened these effects in high glucose-cultured HMCs. Sar relieved DN in rat through inhibition of the NLRP3 inflammasome and NF-κB by down-regulating PAR-1 in kidney. [Display omitted]